El feudalismo político del sistema confesional libanés - Jalloul Muro, Hana (UNISCI Discussion Papers, 2008)
This article tries to explain the complex Lebanese confessional system, an obsolete system whicy today continues to condition the life of the Lebanese population, in the the religious, political, social and economic areas.